PROBLEMATIKA EFEKTIVITAS TIM KERJA GURU DALAM MEWUJUDKAN VISI DAN MISI SEKOLAH - Suntama Putra; Mukhtar; Kasful Anwar; Mahmud MY (Jurnal Genta Mulia, 2024)
This paper aims to discuss the effectiveness of the teacher work team in realizing the school's vision andmission. The focus of this paper is to discuss the factors that cause the effectiveness of teacher work teamsthat do not run according to school expectations and strategies in managing effective teacher work teamsin schools. This research method uses Library Research or literature research by collecting various data andliteracy needed. The results of this study show that the effectiveness of the teacher's work team is strongly influenced by several factors which include internal factors and external factors of team members. Internalfactors such as leadership, communication, skills and abilities as well as conflicts between teachers candirectly affect the effectiveness of work teams. While external factors such as school culture, resources,common goals and work environment can affect the performance of the teacher's work team indirectlythrough internal factors. The effectiveness of the teacher work team will not always run well and inaccordance with the expectations and vision and mission of the school. Therefore, it requires skills inmanaging effective work teams by: Fostering mutual trust between teachers, equalizing the vision andmission of each member of the teacher team, building good communication between teacher teams,understanding responsibilities between teacher team members, conducting regular monitoring andevaluation, giving appreciation and rewards to outstanding team members.